Proceedings of the Frontiers of Retrovirology Conference 2016. Issue 1 (September 2016) - Zurnic, Irena; Hütter, Sylvia; Lehmann, Ute; Stanke, Nicole; Reh, Juliane; Kern, Tobias; Lindel, Fabian; Gerresheim, Gesche; Hamann, Martin; Müllers, Erik; Lesbats, Paul; Cherepanov, Peter; et al.
Table of contents Oral presentations Session 1: Entry & uncoating O1 Host cell polo-like kinases (PLKs) promote early prototype foamy virus (PFV) replication Irena Zurnic, Sylvia Hütter, Ute Lehmann, Nicole Stanke, Juliane Reh, Tobias Kern, Fabian Lindel, Gesche Gerresheim, Martin Hamann, Erik Müllers, Paul Lesbats, Peter Cherepanov, Erik Serrao, Alan Engelman, Dirk Lindemann O2 A novel entry/uncoating assay reveals the presence of at least two species of viral capsids during synchronized HIV-1 infection Claire Da Silva Santos, Kevin Tartour, Andrea Cimarelli O3 Dynamics of nuclear envelope association and nuclear import of HIV-1 complexes Rya Burdick, Jianbo Chen, Jaya Sastri, Wei-Shau Hu, Vinay Pathak O4 Human papillomavirus protein E4 potently enhances the susceptibility to HIV infection Oliver T. Keppler Session 2: Reverse transcription & integration O5 Structure and function of HIV-1 integrase post translational modifications Karine Pradeau, Sylvia Eiler, Nicolas Levy, Sarah Lennon, Sarah Cianferani, Stéphane Emiliani, Marc Ruff O6 Regulation of retroviral integration by RNA polymerase II associated factors and chromatin structure Vincent Parissi Session 3: Transcription and latency O7 A novel single-cell analysis pipeline to identify specific biomarkers of HIV permissiveness Sylvie Rato, Antonio Rausell, Miguel Munoz, Amalio Telenti, Angela Ciuffi O8 A capsid-dependent integration program linking T cell activation to HIV-1 gene expression Alexander Zhyvoloup, Anat Melamed, Ian Anderson, Delphine Planas, Janos Kriston-Vizi, Robin Ketteler, Chen-Hsuin Lee, Andy Merritt, Petronela Ancuta, Charles Bangham, Ariberto Fassati O9 Characterisation of new RNA polymerase III and RNA polymerase II transcriptional promoters in the Bovine Leukemia Virus genome Anthony Rodari, Benoit Van Driessche, Mathilde Galais, Nadége Delacourt, Sylvain Fauquenoy, Caroline Vanhulle, Anna Kula, Arsène Burny, Olivier Rohr, Carine Van Lint O10 Tissue-specific dendritic cells differentially modulate latent HIV-1 reservoirs Thijs van Montfort, Renee van der Sluis, Dave Speijer, Ben Berkhout Session 4: RNA trafficking & packaging O11 A novelcis -acting element affecting HIV replication Bo Meng, Andrzej Rutkowski, Neil Berry, Lars Dölken, Andrew Lever O12 Tolerance of HIV's late gene expression towards stepwise codon adaptation Thomas Schuster, Benedikt Asbach, Ralf Wagner Session 5: Assembly & release O13 Importance of the tax-inducible actin-bundling protein fascin for transmission of human T cell leukemia virus Type 1 (HTLV-1) Christine Gross, Veit Wiesmann, Martina Kalmer, Thomas Wittenberg, Jan Gettemans, Andrea K. Thoma-Kress O14 Lentiviral nef proteins antagonize TIM-mediated inhibition of viral release Minghua Li, Eric O. Freed, Shan-Lu Liu Session 6: Pathogenesis & evolution O15 SEVI and semen prolong the half-life of HIV-1 Janis Müller, Jan Münch O16 CD169+ macrophages mediate retrovirustrans -infection of permissive lymphocytes to establish infection in vivo Xaver Sewald, Pradeep Uchil, Mark Ladinsky, Jagadish Beloor, Ruoxi Pi, Christin Herrmann, Nasim Motamedi, Thomas Murooka, Michael Brehm, Dale Greiner, Thorsten Mempel, Pamela Bjorkman, Priti Kumar, Walther Mothes O17 Efficient replication of avpu containing SIVagm construct in African Green Monkeys requires an HIV-1nef gene Simone Joas, Erica Parrish, Clement Wesley Gnanadurai, Edina Lump, Christina M. Stürzel, Nicholas F. Parrish, Ulrike Sauermann, Katharina Töpfer, Tina Schultheiss, Steven Bosinger, Guido Silvestri, Cristian Apetrei, Nicholas Huot, Michaela Müller-Trutwin, Daniel Sauter, Beatrice H. Hahn, Christiane Stahl-Hennig, Frank Kirchhoff O18 Reprogramming initiates mobilization of endogenous mutagenic LINE-1, Alu and SVA retrotransposons in human induced pluripotent stem cells with consequences for host gene expression Gerald Schumann, Sabine Jung-Klawitter, Nina V. Fuchs, Kyle R. Upton, Martin Muñoz-Lopez, Ruchi Shukla, Jichang Wang, Marta Garcia-Canadas, Cesar Lopez-Ruiz, Daniel J. Gerhardt, Attila Sebe, Ivana Grabundzija, Patricia Gerdes, Sylvia Merkert, Andres Pulgarin, Anja Bock, Ulrike Held, Anett Witthuhn, Alexandra Haase, Ernst J. Wolvetang, Ulrich Martin, Zoltán Ivics, Zsuzsanna Izsvák, J. Garcia-Perez, Geoffrey J. Faulkner O19 NF-κB activation induces expression of human endogenous retrovirus and particle production Tara Hurst, Aris Katzourakis, Gkikas Magiorkinis Session 7a and b: Innate sensing & intrinsic immunity O20 Identification of the phosphatase acting on T592 in SAMHD1 during M/G1 transition Kerstin Schott, Rita Derua, Janna Seifried, Andreas Reuter, Heike Schmitz, Christiane Tondera, Alberto Brandariz-Nuñez, Felipe Diaz-Griffero, Veerle Janssens, Renate König O21 Vpx overcomes a SAMHD1-independent block to HIV reverse transcription that is specific to resting CD4 T cells Hanna-Mari Baldauf, Lena Stegmann, Sarah-Marie Schwarz, Maud Trotard, Margarethe Martin, Gina Lenzi, Manja Burggraf, Xiaoyu Pan, Oliver I. Fregoso, Efrem S. Lim, Libin Abraham, Elina Erikson, Laura Nguyen, Ina Ambiel, Frank Rutsch, Renate König, Baek Kim, Michael Emerman, Oliver T. Fackler, Oliver T. Keppler O22 The role of SAMHD1 in antiviral restriction and immune sensing in the mouse Sabine Wittmann, Rayk Behrendt, Bianca Volkmann, Kristin Eissmann, Thomas Gramberg O23 T cells expressing reduced restriction factors are preferentially infected in therapy naïve HIV-1 patients Sebastian Bolduan, Herwig Koppensteiner, Stefanie Regensburg, Ruth Brack-Werner, Rika Draenert, Michael Schindler O24 cGAS-mediated innate immunity spreads through HIV-1 env-induced membrane fusion sites from infected to uninfected primary HIV-1 target cells Aurélie Ducroux, Shuting Xu, Aparna Ponnurangam, Sergej Franz, Angelina Malassa, Ellen Ewald, Christine Goffinet O25 Perturbation of innate RNA and DNA sensing by human T cell leukemia virus type 1 oncoproteins Sin-Yee Fung, Ching-Ping Chan, Chun-Kit Yuen, Kin-Hang Kok, Chin-Ping Chan, Dong-Yan Jin O26 Induction and anti-viral activity of Interferon α subtypes in HIV-1 infection Ulf Dittmer O27 Vpu-mediated counteraction of tetherin is a major determinant of HIV-1 interferon resistance Dorota Kmiec, Shilpa Iyer, Christina Stürzel, Daniel Sauter, Beatrice Hahn, Frank Kirchhoff O28 DNA repair protein Rad18 restricts HIV-1 and LINE-1 life cycle Yasuo Ariumi, Mariko Yasuda-Inoue, Koudai Kawano, Satoshi Tateishi, Priscilla Turelli O29 Natural mutations inIFITM3 allow escape from post-translational regulation and toggle antiviral specificity Alex Compton, Nicolas Roy, Françoise Porrot, Anne Billet, Nicoletta Casartelli, Jacob Yount, Chen Liang, Oliver Schwartz Session 8: Adaptive immunity & immune evasion O30 Observing evolution in HIV-1 infection: phylogenetics and mutant selection windows to infer the influence of the autologous antibody response on the viral quasispecies Carsten Magnus, Lucia Reh, Penny Moore, Therese Uhr, Jacqueline Weber, Lynn Morris, Alexandra Trkola O31 Dose and subtype specific analyses of the anti-HIVeffects of IFN-alpha family members Rashel V. Grindberg, Erika Schlaepfer, Gideon Schreiber, Viviana Simon, Roberto F. Speck Session 9: Novel antiviral strategies O32 LEDGIN-mediated inhibition of the integrase-LEDGF/p75 interaction reduces reactivation of residual latent HIV Zeger Debyser, Lenard Vranckx, Jonas Demeulemeester, Suha Saleh, Eric Verdin, Anna Cereseto, Frauke Christ, Rik Gijsbers O33 NKG2D-mediated clearance of reactivated viral reservoirs by natural killer cells O34 Inhibition of HIV reactivation in brain cells by AAV-mediated delivery of CRISPR/Cas9 O35 CRISPR-Cas9 as antiviral: potent HIV-1 inhibition, but rapid virus escape and the subsequent design of escape-proof antiviral strategies Ben Berkhout, Gang Wang, Na Zhao, Atze T. Das Session 10: Recent advances in HIV vaccine development O36 Priming with a potent HIV-1 DNA vaccine frames the quality of T cell and antibody responses prior to a poxvirus and protein boost Benedikt Asbach, Josef Köstler, Beatriz Perdiguero, Mariano Esteban, Bertram L. Jacobs, David C. Montefiori, Celia C. LaBranche, Nicole L. Yates, Georgia D. Tomaras, Guido Ferrari, Kathryn E. Foulds, Mario Roederer, Gary Landucci, Donald N. Forthal, Michael S. Seaman, Natalie Hawkins, Steven G. Self, Sanjay Phogat, James Tartaglia, Susan W. Barnett, Brian Burke, Anthony D. Cristillo, Song Ding, Jonathan L. Heeney, Giuseppe Pantaleo, Ralf Wagner O37 Passive immunisation with a neutralising antibody against HIV-1 Env prevents infection of the first cells in a mucosal challenge rhesus monkey model Christiane Stahl-Hennig, Viktoria Stab, Armin Ensser, Ulrike Sauermann, Bettina Tippler, Dennis Burton, Matthias Tenbusch, Klaus Überla O38 HIV antibody Fc-glycoforms drive B cell affinity maturation Galit Alter, Giuseppe Lofano, Anne-Sophie Dugast, Viraj Kulkarni, Todd Suscovich Poster presentations Topic 1: Entry & uncoating P1 Dynein light chain is required for murine leukemia virus infection Tatiana Opazo, Felipe Barraza, Diego Herrera, Andrea Garces, Tomas Schwenke, Diego Tapia, Jorge Cancino, Gloria Arriagada P2 Peptide paratope mimics of the broadly neutralising HIV-1 antibody b12 Christina Haußner, Dominik Damm, Anette Rohrhofer, Barbara Schmidt, Jutta Eichler P3 Investigating cellular pathways involved in the transmission of HIV-1 between dendritic cells and T cells using RNAi screening techniques Rebecca Midgley, James Wheeldon, Vincent Piguet P4 Co-receptor tropism in HIV-1, HIV-2 monotypic and dual infections Priyanka Khopkar, Megha Rohamare, Smita Kulkarni P5 Characterisation of the role of CIB1 and CIB2 as HIV-1 helper factors Ana Godinho-Santos, Allan Hance, Joao Goncalves, Fabrizio Mammano P6 Buffering deleterious polymorphisms in the highly constrained C2 region of HIV-1 envelope by the flexible V3 domain Romain Gasser, Meriem Hamoudi, Martina Pellicciotta, Zhicheng Zhou, Clara Visdeloup, Philippe Colin, Martine Braibant, Bernard Lagane, Matteo Negroni P7 Entry inhibition of HERV-K(HML-2) by an Env-IgG fusion protein Jula Wamara, Norbert Bannert Topic 2: Reverse transcription & integration P8 The R263K/H51Y resistance substitutions in HIV integrase decreases levels of integrated HIV DNA over time Thibault Mesplede, Nathan Osman, Kaitlin Anstett, Jiaming Calvin Liang, Hanh Thi Pham, Mark Wainberg P9 The Retrovirus Integration Database (RID) Wei Shao, Jigui Shan, Mary Kearney, Xiaolin Wu, Frank Maldarelli, John Mellors, Brian Luke, John Coffin, Stephen Hughes P10 The small molecule 3G11 inhibits HIV-1 reverse transcription Thomas Fricke, Silvana Opp, Caitlin Shepard, Dmitri Ivanov, Baek Kim, Jose Valle-Casuso, Felipe Diaz-Griffero P11 Dual and opposite regulation of HIV-1 integration by hRAD51: impact on therapeutical approaches using homologous DNA repair modulators Vincent Parissi P12 A flexible motif essential for integration by HIV-1 integrase Marine Kanja, Pierre Cappy, Matteo Negroni, Daniela Lener P13 Interaction between HIV-1 integrase and the host protein Ku70: identification of the binding site and study of the influence on integrase-proteasome interplay Ekaterina Knyazhanskaya, Andrey Anisenko, Timofey Zatsepin, Marina Gottikh P14 Normalisation based method for deep sequencing of somatic retroelement integrations in human genome Alexander Komkov, Anastasia Minervina, Gaiaz Nugmanov, Vadim Nazarov, Konstantin Khodosevich, Ilgar Mamedov, Yuri Lebedev Topic 3: Transcription and latency P15 BCA2/RABRING7 restricts HIV-1 transcription by preventing the nuclear translocation of NF-κB Marta Colomer-Lluch, Ruth Serra-Moreno P16 MATR3 post-transcriptional regulation of HIV-1 transcription during latency Ambra Sarracino, Anna Kula, Lavina Gharu, Alexander Pasternak, Carine Van Lint, Alessandro Marcello P17 HIV-1 tat intersects the SUMO pathway to regulate HIV-1 promoter activity Ann Marie McCartin, Anurag Kulkarni, Valentin Le Douce, Virginie Gautier P18 Conservation in HIV-1 Vpr guides tertiary gRNA folding and alternative splicing Ann Baeyens, Evelien Naessens, Anouk Van Nuffel, Karin Weening, Anne-Marie Reilly, Eva Claeys, Wim Trypsteen, Linos Vandekerckhove, Sven Eyckerman, Kris Gevaert, Bruno Verhasselt P19 The majority of reactivatable latent HIV are genetically distinct Hoi Ping Mok, Nicholas Norton, Axel Fun, Jack Hirst, Mark Wills, Andrew Lever P20 Do mutations in thetat exonic splice enhancer contribute to HIV-1 latency? Nicholas Norton, Hoi Ping Mok, Jack Hirst, Andrew Lever P21 Culture-to-Ct: A fast and direct RT-qPCR HIV gene reactivation screening method using primary T cell culture Valentin Le Douce, Ann Marie McCartin, Virginie Gautier P22 A novel approach to define populations of early silenced proviruses Dalibor Miklik, Filip Senigl, Jiri Hejnar Topic 4: RNA trafficking & packaging P23 Functional analysis of the structure and conformation of HIV-1 genome RNA DIS Jun-ichi Sakuragi, Sayuri Sakuragi, Masaru Yokoyama, Tatsuo Shioda, Hironori Sato P24 Regulation of foamy viralenv splicing controlsgag andpol expression Jochen Bodem, Rebecca Moschall, Sarah Denk, Steffen Erkelenz, Christian Schenk, Heiner Schaal Topic 5: Assembly & release P25 Transfer of HTLV-1 p8 to target T cells depends on VASP: a novel interaction partner of p8 Norbert Donhauser, Ellen Socher, Sebastian Millen, Heinrich Sticht, Andrea K. Thoma-Kress P26 COL4A1 and COL4A2 are novel HTLV-1 tax targets with a putative role in virus transmission Christine Gross, Sebastian Millen, Melanie Mann, Klaus Überla, Andrea K. Thoma-Kress P27 The C terminus of foamy virus gag protein is required for particle formation, and virus budding: starting assembly at the C terminus? Guochao Wei, Matthew J. Betts, Yang Liu, Timo Kehl, Robert B. Russell, Martin Löchelt P28 Generation of an antigen-capture ELISA and analysis of Rec and Staufen-1 effects on HERV-K(HML-2) virus particle production Oliver Hohn, Saeed Mostafa, Kirsten Hanke, Stephen Norley, Norbert Bannert P29 Antagonism of BST-2/tetherin is a conserved function of primary HIV-2 Env glycoproteins Chia-Yen Chen, Masashi Shingai, Pedro Borrego, Nuno Taveira, Klaus Strebel P30 Mutations in the packaging signal region of the HIV-1 genome cause a late domain mutant phenotype Chris Hellmund, Bo Meng, Andrew Lever P31 p6 regulates membrane association of HIV-1 gag Melanie Friedrich, Friedrich Hahn, Christian Setz, Pia Rauch, Kirsten Fraedrich, Alina Matthaei, Petra Henklein, Maximilian Traxdorf, Torgils Fossen, Ulrich Schubert Topic 6: Pathogenesis & evolution P32 Molecular and structural basis of protein evolution during viral adaptation Aya Khwaja, Meytal Galilee, Akram Alian P33 HIV-1 enhancement and neutralisation by soluble gp120 and its role for the selection of the R5-tropic "best fit" Birco Schwalbe, Heiko Hauser, Michael Schreiber P34 An insertion of seven amino acids in the Env cytoplasmic tail of Human Immunodeficiency Virus type 2 (HIV-2) selected during disease progression enhances viral replication François Dufrasne, Mara Lucchetti, Patrick Goubau, Jean Ruelle P35 Cell-associated HIV-1 unspliced to multiply spliced RNA ratio at 12 weeks ART correlates with markers of immune activation and apoptosis and predicts the CD4 T-cell count at 96 weeks ART Mirte Scherpenisse, Ben Berkhout, Alexander Pasternak P36 Faster progression in non-B subtype HIV-1-infected patients than Korean subclade of subtype B is accompanied by higher variation and no induction of gross deletion in non-Bnef gene by Korean red ginseng treatment Young-Keol Cho, Jungeun Kim, Daeun Jeong P37 Aberrant expression of ERVWE1 endogenous retrovirus and overexpression of TET dioxygenases are characteristic features of seminoma Katerina Trejbalova, Martina Benesova, Dana Kucerova, Zdenka Vernerova, Rachel Amouroux, Petra Hajkova, Jiri Hejnar P38 Life history of the oldest lentivirus: characterisation of ELVgv integrations and theTRIM5 selection pattern in dermoptera Daniel Elleder, Tomas Hron, Helena Farkasova, Abinash Padhi, Jan Paces P39 Characterisation of a highly divergent endogenous retrovirus in the equine germ line Henan Zhu, Robert Gifford, Pablo Murcia P40 The emergence of pandemic retroviral infection in small ruminants Maria Luisa Carrozza, Anna-Maria Niewiadomska, Maurizio Mazzei, Mounir Abi-Said, Joseph Hughes, Stéphane Hué, Robert Gifford P41 Near full-length genome (NFLG) Characterisation of HIV-1 subtype B identified in South Africa Adetayo Obasa, Graeme Jacobs, Susan Engelbrecht P42 Acquisition of Vpu-mediated tetherin antagonism by an HIV-1 group O strain Katharina Mack, Kathrin Starz, Daniel Sauter, Matthias Geyer, Frederic Bibollet-Ruche, Christina Stürzel, Marie Leoz, Jean Christophe Plantier, Beatrice H. Hahn, Frank Kirchhoff P43 The human endogenous retrovirus type K is involved in cancer stem cell markers expression and in human melanoma malignancy Ayele Argaw-Denboba, Emanuela Balestrieri, Annalucia Serafino, Ilaria Bucci, Chiara Cipriani, Corrado Spadafora, Paolo Sinibaldi-Vallebona, Claudia Matteucci P44 Natural infection of Indian non-human primates by unique lentiviruses S. Nandi Jayashree, Ujjwal Neogi, Anil K. Chhangani, Shravan Sing Rathore, Bajrang R. J. Mathur P45 Free cervical cancer screening among HIV-positive women receiving antiretroviral treatment in Nigeria Adeyemi Abati P46 Molecular evolutionary status of feline immunodeficiency virus in Turkey B. Taylan Koç, Tuba Çiğdem Oğuzoğlu Topic 7: Innate sensing & intrinsic immunity P47 Cell-to-cell contact with HTLV-1-infected T cells reduces dendritic cell immune functions and contributes to infectionin trans . Takatoshi Shimauchi, Stephan Caucheteux, Jocelyn Turpin, Katja Finsterbusch, Charles Bangham, Yoshiki Tokura, Vincent Piguet P48 Deciphering the mechanisms of HIV-1 exacerbation induced byMycobacterium tuberculosis in monocytes/macrophages Shanti Souriant, Luciana Balboa, Karine Pingris, Denise Kviatcowsky, Brigitte Raynaud-Messina, Céline Cougoule, Ingrid Mercier, Marcelo Kuroda, Pablo González-Montaner, Sandra Inwentarz, Eduardo Jose Moraña, Maria del Carmen Sasiain, Olivier Neyrolles, Isabelle Maridonneau-Parini, Geanncarlo Lugo-Villarino, Christel Vérollet P49 The SAMHD1-mediated inhibition of LINE-1 retroelements is regulated by phosphorylation Alexandra Herrmann, Sabine Wittmann, Caitlin Shepard, Dominique Thomas, Nerea Ferreirós Bouzas, Baek Kim, Thomas Gramberg P50 Activities of nuclear envelope protein SUN2 in HIV infection Xavier Lahaye, Anvita Bhargava, Takeshi Satoh, Matteo Gentili, Silvia Cerboni, Aymeric Silvin, Cécile Conrad, Hakim Ahmed-Belkacem, Elisa C. Rodriguez, Jean-François Guichou, Nathalie Bosquet, Matthieu Piel, Roger Le Grand, Megan King, Jean-Michel Pawlotsky, Nicolas Manel P51 Activation of TLR7/8 with a small molecule agonist induces a novel restriction to HIV-1 infection of monocytes Henning Hofmann, Benedicte Vanwalscappel, Nicolin Bloch, Nathaniel Landau P52 Steady state between the DNA polymerase and Rnase H domain activities of reverse transcriptases determines the sensitivity of retroviruses to inhibition by APOBEC3 proteins Stanislav Indik, Benedikt Hagen P53 HIV restriction in mature dendritic cells is related to p21 induction and p21-mediated control of the dNTP pool and SAMHD1 activity. José Carlos Valle-Casuso, Awatef Allouch, Annie David, Françoise Barré-Sinoussi, Michaela Müller-Trutwin, Monsef Benkirane, Gianfranco Pancino, Asier Saez-Cirion P54 IFITM protens restrict HIV-1 protein synthesis Wing-Yiu Lee, Chen Liang, Richard Sloan P55 Characterisation and functional analysis of the novel restriction factor Serinc5 Bianca Schulte, Silvana Opp, Felipe Diaz-Griffero P56 piRNA sequences are common in Human Endogenous Retroviral Sequences (HERVs): An antiretroviral restriction mechanism? Jonas Blomberg, Luana Vargiu, Patricia Rodriguez-Tomé, Enzo Tramontano, Göran Sperber P57 Ferroportin restricts HIV-1 infection in sickle cell disease Namita Kumari, Tatiana Ammosova, Sharmeen Diaz, Patricia Oneal, Sergei Nekhai P58 APOBEC3G modulates the response to antiretroviral drugs in humanized mice Audrey Fahrny, Gustavo Gers-Huber, Annette Audigé, Roberto F. Speck, Anitha Jayaprakash, Ravi Sachidanandam, Matt Hernandez, Marsha Dillon-White, Viviana Simon P59 High-throughput epigenetic analysis of evolutionarily young endogenous retrovirus presents in the mule deer(Odocoileus hemionus ) genome Tomas Hron, Helena Farkasova, Daniel Elleder P60 Characterisation of the expression of novel endogenous retroviruses and immune interactions in a macaque model Neil Berry, Emmanuel Maze, Claire Ham, Neil Almond, Greg Towers, Robert Belshaw P61 HIV-1 restriction by orthologs of SERINC3 and SERINC5 Patrícia de Sousa-Pereira, Joana Abrantes, Massimo Pizzato, Pedro J. Esteves, Oliver T. Fackler, Oliver T. Keppler, Hanna-Mari Baldauf P62 TRIM19/PML restricts HIV infection in a cell type-dependent manner Bianca Volkmann, Tanja Kahle, Kristin Eissmann, Alexandra Herrmann, Sven Schmitt, Sabine Wittmann, Laura Merkel, Nina Reuter, Thomas Stamminger, Thomas Gramberg P63 Recent invasion of the mule deer genome by a retrovirus Helena Farkasova, Tomas Hron, Daniel Elleder P64 Does the antiviral protein SAMHD1 influence mitochondrial function? Ilaria Dalla Rosa, Kate Bishop, Antonella Spinazzola, Harriet Groom P65 cGAMP transfers intercellularly via HIV-1 Env-mediated cell–cell fusion sites and triggers an innate immune response in primary target cells Shuting Xu, Aurélie Ducroux, Aparna Ponnurangam, Sergej Franz, Gabrielle Vieyres, Mathias Müsken, Thomas Zillinger, Angelina Malassa, Ellen Ewald, Veit Hornung, Winfried Barchet, Susanne Häussler, Thomas Pietschmann, Christine Goffinet P66 Pre-infection transcript levels ofFAM26F in PBMCS inform about overall plasma viral load in acute and postacute phase after SIV-infection Ulrike Sauermann, Aneela Javed, Nicole Leuchte, Gabriela Salinas, Lennart Opitz, Christiane Stahl-Hennig, Sieghart Sopper P67 Sequence-function analysis of three T cell receptors targeting the HIV-1 p17 epitope SLYNTVATL Christiane Mummert, Christian Hofmann, Angela G. Hückelhoven, Silke Bergmann, Sandra M. Müller-Schmucker, Ellen G. Harrer, Jan Dörrie, Niels Schaft, Thomas Harrer P68 An immunodominant region of the envelope glycoprotein of small ruminant lentiviruses may function as decoy antigen Laure Cardinaux, M.-L. Zahno, H.-R. Vogt, R. Zanoni, G. Bertoni P69 Impact of immune activation, immune exhaustion, broadly neutralising antibodies and viral reservoirs on disease progression in HIV-infected children Maximilian Muenchhoff, Philip Goulder, Oliver Keppler Topic 9: Novel antiviral strategies P70 Identification of natural compounds as new antiviral products by bioassay-guided fractionation Alexandra Herrmann, Stephanie Rebensburg, Markus Helfer, Michael Schindler, Ruth Brack-Werner P71 The PPARG antagonism disconnects the HIV replication and effector functions in Th17 cells Yuwei Zhang, Huicheng Chen, Delphine Planas, Annie Bernier, Annie Gosselin, Jean-Pierre Routy, Petronela Ancuta P72 Characterisation of a multiresistant subtype AG reverse transcriptase: AZT resistance, sensitivity to RNase H inhibitors and inhibitor binding Birgitta Wöhrl, Anna Schneider, Angela Corona, Imke Spöring, Mareike Jordan, Bernd Buchholz, Elias Maccioni, Roberto Di Santo, Jochen Bodem, Enzo Tramontano, Kristian Schweimer P73 Insigths into the acetylation pattern of HDAC inhibitors and their potential role in HIV therapy Christian Schölz, Brian Weinert, Sebastian Wagner, Petra Beli, Yasuyuki Miyake, Jun Qi, Lars Jensen, Werner Streicher, Anna McCarthy, Nicholas Westwood, Sonia Lain, Jürgen Cox, Patrick Matthias, Matthias Mann, James Bradner, Chunaram Choudhary P74 HPV-derived and seminal amyloid peptides enhance HIV-1 infection and impair the efficacy of broadly neutralising antibodies and antiretroviral drugs Marcel Stern, Oliver T. Keppler P75 D(−)lentiginosine inhibits both proliferation and virus expression in cells infected by HTLV-1 in vitro Elena Valletta, Caterina Frezza, Claudia Matteucci, Francesca Marino-Merlo, Sandro Grelli, Anna Lucia Serafino, Antonio Mastino, Beatrice Macchi P76 HIV-1 resistance analyses of the Cape Winelands districts, South Africa Sello Mikasi, Graeme Jacobs, Susan Engelbrecht Topic 10: Recent advances in HIV vaccine development P77 Induction of complex retrovirus antigen-specific immune responses by adenovirus-based vectors depends on the order of vector administration Meike Kaulfuß, Sonja Windmann, Wibke Bayer P78 Direct impact of structural properties of HIV-1 Env on the regulation of the humoral immune response Rebecca Heß, Michael Storcksdieck gen. Bonsmann, Viktoria Stab, Carsten Kirschning, Bernd Lepenies, Matthias Tenbusch, Klaus Überla P79 Lentiviral virus-like particles mediate gerenration of T-follicular helper cellsin vitro Anne Kolenbrander, Klaus Überla, Vladimir Temchura P80 Recruitment of HIV-1 Vpr to DNA damage sites and protection of proviral DNA from nuclease activity Kenta Iijima, Junya Kobayashi, Yukihito Ishizaka